Acquired hypercoagulable state in renal transplant recipients - Kazory, Amir; Ducloux, Didier (Thrombosis and Haemostasis, 2004)
Stable renal transplant recipients manifest a chronic hypercoagulable state with an increased risk of thromboembolic complications, which appears to be multifactorial. While this group of patients could present the known risk factors for thromboembolism in the general population (e.g. diabetes, cancer, pregnancy), they may also suffer from other situations which are mostly related to transplantation and are consequently specific to them. Here, we review briefly the clinical aspects and controversies of the most important of these factors including immunosuppressive agents, antiphospholipid antibodies, hyperhomocysteinemia, pre-transplant dialysis modality, and posttransplant erythrocytosis. In addition, other more recent topics including hypercysteinemia, recurrent proteinuria, and acute CMV infection are discussed.
Keywords: Renal transplantation; thromboembolism; hypercoagulability; thrombosis